Enhancing Students' Argumentative Writing Performance And Critical Thinking Skills Through The Incorporation Of Concept Mapping And Content-Based Instruction - Maekong, Nureeyah (2017)
This study emphasizes the writing planning strategy, derived from cognitive process of writing, meaningful learning theory, and critical thinking skill, implemented by the incorporation of concept mapping strategy (CM) and content-based instruction (CBI). The purpose of this study is to investigate the effects of this strategy on student‟s writing performances and critical thinking skills, in planning argumentative writing. This study employed a mixed-method research methodology on 78 research participants which is designed into two groups, experimental (N=42), and control (N=36) groups. These research participants are intact groups of pre-university English program students at English Center, International language Academy, Fatoni Unversity Thailand, which were taking English writing course of English Preparatory level 3 (EP 3), academic year 2014.